P1-S3.11 Factors associated with death among infants with neonatal herpes reported in New York City, 2006−2010. (10th July 2011) - Schillinger, J; Handel, S; Washburn, K; Klingler, E; Blank, S; Pathela, P
Abstract : Background: Neonatal herpes simplex virus infection (nHSV) has a high case fatality rate. In New York City (NYC), healthcare providers (HCP) and laboratories report nHSV to the Health Department; incidence is highest among infants born to black non-Hispanic (NH), and young women. We analysed nHSV cases to identify factors associated with death. Methods: nHSV cases in infants <60 days were investigated by HCP interview and abstraction of labour and delivery, outpatient, inpatient, vital records. Bivariate and multivariate models estimated associations between death and demographic, clinical, and provider factors. Results: During 2006−2010, 71 laboratory-confirmed nHSV cases were reported; 43/71 (55%) were male, 29/71 (41%) HSV type 1, 28/71 (39%) HSV type 2, and 14/71 (20%) untyped. Among 58 cases with recorded maternal race/ethnicity, 19 (33%) were white NH, 25 (43%) were black NH, and 15 (26%) were Hispanic. Fourteen of the 71 (20%) cases died; 10 of the deaths (71%) were among infants born to black NH women. There was a significant association between death and disseminated disease (vs skin/eye/mucous membrane, central nervous system, or congenital infection) (OR 25.8, 95% CI 4.5 to 148.9), black NH maternal race (OR 10.0, 95% CI 2.4 to 41.0), preterm birth (OR 7.1, 95% CI 1.9 to 26.5), age <7 days at first symptom (OR 5.8, 95% CI 1.5 to 23.3), maternal age <26 (OR 3.02, 95% CI 0.8 to 10.86), vaginal delivery (OR 0.2, 95% CI 0.1 to 0.8), and presence of infant herpes lesions (OR 0.2, 95% CI 0.04 to 0.6). Infant sex, fever, viral type, admitting hospital type (academic vs non-academic), illness within 24 h of birth, and duration rupture of membranes were not associated with death. After adjusting for preterm birth, black NH maternal race remained associated with a significantly higher risk for death (OR 7.2 95% CI 1.6—to 31.4, p=0.009). Disseminated disease also remained significantly associated with death after adjusting for preterm birth, and age at first symptom (OR 26.6, 95% CI 3.6 to 196.5, p=0.001). Conclusions: Our data suggest a significant racial disparity in nHSV fatality, only partly explained by preterm births among black NH mothers. Further investigation should examine if care-seeking or provider characteristics contribute to these disparities. Black NH maternal race may be a marker for recently acquired herpes infection, with a high organism load at delivery. Disseminated disease is strongly, and independently, associated with fatality.